Re-processing 1500 years of Torneträsk density and ring-width data - Håkan Grudd; Thomas M Melvin; Keith R Briffa (Stockholm University, 2015)
The analysis of existing and new maximum-latewood-density (MXD) and tree-ring width (TRW) data from the Torneträsk region of northern Sweden and the construction of 1500 year chronologies.
Keywords: Environmental Science; Paleoclimatology; Physical Geography; Climate Science; Climate Science; Klimatvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap